Children and adolescents at risk for seclusion and restraint in inpatient psychiatric treatment: a case control study - Klara Czernin; Anselm Bründlmayer; Anna Oster; Josef S. Baumgartner; Paul L. Plener (BMC, 2024)
Abstract To reduce coercion in acute inpatient child and adolescent psychiatric units, a better understanding of individuals at risk for seclusion and/or restraint (S/R) is needed. We report data on the proportion of patients secluded/restrained and factors associated with higher risk of S/R. Identifying preventative mechanisms through risk stratification upon inpatient admission can aid the training of mental health professionals, and support shaping specific workflows for at-risk populations for example by joint crisis plans or post-coercion review sessions. Methods: A case-control study included all admissions (n = 782) to a department of child and adolescent psychiatry within 36 months between 2019 and 2022. Data on age, sex, out of home care, primary and comorbid ICD-10 diagnoses, length of stay, prior/multiple admissions were compared between admissions with and without S/R using chi square tests for categorical and t-tests for continuous variables. Uni- and multivariate binary logistic regression models were computed. Results: The overall proportion of S/R was 12.8% (n = 100). Females (p = 0.001), patients in out of home care (p < 0.001), with prior admission (p < 0.001), Post-traumatic stress disorder (PTSD; p < 0.001) and Borderline personality disorder (BPD; p < 0.001) were at a significantly higher risk of S/R. Length of stay in days (OR 1.01), out of home care (OR 3.85), PTSD (OR 6.20), BPD (OR 15.17), Attention deficit hyperactivity disorder (ADHD)/conduct disorder (OR 4.29), and manic episode/bipolar disorder (OR 36.41) were significantly associated with S/R in multivariate regression. Conclusions: Child and adolescent psychiatric staff should consider risk factors when using coercive measures. Patients with PTSD and/or BPD are the most vulnerable subgroups. Training of professionals and clinical practice need to be adapted in order to prevent the use of S/R and its potential hazards.